Analisis Potensi Ekonomi dan Penyusunan Grand Strategy Investasi di Kota Semarang - Hardiwinoto Hardiwinoto (STIE Widya Manggala, 2011)
This study aimed to analyze the economic potential and preparation of the grand strategy of investing in the city of Semarang. Analytical methods used were AHP (Analytical Hierarchy Process) and SWOT (Strength, Weakness, Opportunity, Threat). The Data was obtained by conducting in-depth interviews on stakeholders, and then conducted focus group discussions (FGD). Besides using AHP and SWOT analysis as well as the FGDs also conducted a study visit to the city of Surabaya. The study recommends that the city of Semarang needs to be developed center of trade and means of promotion.